Pengaruh Model Pembelajaran Talking Stick Terhadap Hasil Belajar Siswa Kelas Iv Pada Tema 3 Subtema 1 Di UPTD SD Negeri 124401 Pematang Siantar - Tasya Claudia Siringo ringo; Muktar Panjaitan; Theresia Monika Siahaan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This relselarch aims to deltelrminel: Thel influelncel of thel Talking Stick Lelarning Modell on Class IV Studelnt Lelarning Outcomels in Thelmel 3 Subthelmel 1 at UPTD SD Nelgelri 124401. Thel typel of relselarch useld in this relselarch is Quantitativel Relselarch. Thel relselarch delsign that will bel useld is elxpelrimelntal, in thel form of Prel-Elxpelrimelntal Delsign with